2012
DOI: 10.1186/1749-8090-7-49
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to control air leaks in complex lung surgery: a retrospective review

Abstract: BackgroundIntra-operative air leaks (IOAL) are common complications of pulmonary surgery. The post-operative management of air leaks requires a chest tube which may lead to longer hospitalization, further medical complications, and increased costs. Sealants have been shown to help control intra-operative air leaks and studies have demonstrated a reduction in chest tube duration and/or length of hospital stay. Nevertheless, systematic reviews have not presented sufficient evidence to recommend their general use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
0
18
0
1
Order By: Relevance
“…This compares favorably with the results reported by Allen and colleagues, who observed that 35% of patients experienced freedom from air leak throughout the entire 1-month follow-up, versus only 14% of the control group. Similarly, Klijian performed a retrospective review of a single institution experience comparing patients undergoing lung resection who received intraoperative pleural sealant with those who did not [22]. In individuals with intraoperative air leak, the use of sealant was associated with a significant decrease in the incidence of postoperative air leak (11% in the sealant group versus 58.8% in the control group, p  <0.0001) as well as shorter chest tube duration and hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…This compares favorably with the results reported by Allen and colleagues, who observed that 35% of patients experienced freedom from air leak throughout the entire 1-month follow-up, versus only 14% of the control group. Similarly, Klijian performed a retrospective review of a single institution experience comparing patients undergoing lung resection who received intraoperative pleural sealant with those who did not [22]. In individuals with intraoperative air leak, the use of sealant was associated with a significant decrease in the incidence of postoperative air leak (11% in the sealant group versus 58.8% in the control group, p  <0.0001) as well as shorter chest tube duration and hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…When Progel was utilized, only 11% of the patients continued to have IOAL events, whereas in the control group, 56.8% had persistent leaks. The length of time that a chest tube was required was shorter for the Progel group (1 day compared to 2.5) and the hospital stay was halved; 1.5 days was required for the group treated with Progel versus 3 days for the control group [38]. …”
Section: Sealantsmentioning
confidence: 99%
“…In a single-center, retrospective chart review of prospectively collected data in 121 consecutive patients who underwent lung surgery with and without Progel, preoperative, operative, and 3-month postoperative data were evaluated [17]. The study included adult patients who underwent lung resection including lobectomy, segmentectomy, wedge resection, and decortications between May 2009 and August 2010.…”
Section: Reviewmentioning
confidence: 99%